Analisis Kapasitas dan Dimensi Reservoir PDAM Aurduri - S, Wahyu Marselino; Das, Amsori M; Azanna, Dwitya Okky (Jurnal Talenta Sipil, 2025)
The increasing population in Jambi city every year has an impact on the increasing need for clean water. As a regional drinking water company, PERUMDA Tirta Mayang needs to plan clean water needs and calculate reservoir capacity to meet customer water needs. The purpose of this study is to determine the effective reservoir volume at IPA Aurduri as one of the IPAs with the largest processing capacity, project clean water needs, and calculate the effective reservoir volume for the next 10 years. The projection formula is used to project the needs for the next 10 years. The projection formula used is geometric, arithmetic which will then be selected the best for the projection calculation. IPA Aurduri has a processing capacity of 270 l/s and a total reservoir capacity of 2,500 m3. The projection results for the next 10 years, customer clean water demand is 189,095 lt/sec, and the average daily water requirement is 249,605 lt/sec. The required reservoir volume is 5,400 m3. So PERUMDA needs to increase its capacity by 2,900 m3.